Regenerative potential of autologous platelet-rich fibrin with and without amnion membrane in the treatment of Grade-II furcation defects: A clinicoradiographic study - Jaspreet Kaur; Shalu Chandna Bathla (Wolters Kluwer Medknow Publications, 2018)
Context: Platelet-rich fibrin (PRF), platelet concentrate composed of cytokines and structural glycoproteins trapped within polymerized fibrin meshwork, has the potential to accelerate healing of periodontal tissues. Amnion membrane has also attracted a lot of attention in periodontal regeneration due to the presence of variety of growth factors. Aims: The aim of the study is to evaluate and compare the regenerative potential of autologous PRF with and without amnion membrane in the treatment of Grade II furcation defects. Settings and Design: This was a double-masked randomized, split-mouth design study. Materials and Methods: Fifteen patients with thirty mandibular degree II furcation defects were randomly allotted into Group I (PRF and amnion membrane) and Group II (PRF). Clinical parameters such as plaque index and gingival index-at defect site along with probing pocket depth, and relative attachment level and furcation defect depth were recorded at baseline, 3 months, and 6 months postoperatively. Assessment of radiographic parameters was done at baseline and 6 months postoperatively aided by computer-assisted tomography (Dentascan). Statistical Analysis Used: For intragroup variations, Wilcoxon signed-rank test, and for comparison between the two groups/intergroup variations, Independent t-test and Mann-Whitney test was performed. Results: All clinical and radiographic parameters showed statistically significant improvement at the sites treated with PRF and amnion membrane compared to those with PRF alone. Conclusions: Within the limitation of this study, there was greater pocket reduction, attachment level gain, and bone fill at sites treated with PRF and amnion membrane as compared to PRF alone.